PELAKSANAAN SPONSORSHIP DAMPAKNYA TERHADAP BRAND 3SECOND PADA CLOTHING TRUNOJOYO BANDUNG (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
The implementation of sponsorship is a marketing strategy and innovation company that has an impact on changing the existing competition, where the execution of the company's brand 3second  will have the eyes of the customer added value compared to other companies. Knowing the purpose of this study is the response of respondents to the implementation of sponsorship activities, knowing the brand 3second , and determine how far the implementation of sponsorship impact on brand 3second  at Linecoltd Clothing.The method used is survey with descriptive and verification approaches. The study population numbered 400, and sampling techniques using random sampling to obtain a sample of 80 consumers. Techniques of data collection using interviews, observation, questionnaires and documentation. Analysis method using Pearson product moment and coefficient of determination, as well as t test using SPSS 15.0 for Windows.The results mentioned implementation of sponsorship based on the responses of respondents with good results, while brand 3second  showed good results. Results of analysis showed that the implementation of sponsorship impact on brand 3second  shows the degree of relationship is that of 0574, with the contribution of the impact of 32.94%, and the remaining 67.06% influenced by other factors not examined by the authors.